APPLICATION OF MATRICES IN THE TOURISM MANAGEMENT SYSTEM OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
This article aims to justify the need for the application of matrix-based models in the tourism management system, using the Republic of Armenia as a case study, and to demonstrate their effectiveness, as data-driven decision making, tools for the tourism sector. This study investigates the tourism management system, with a particular focus on the spatial interrelationships of tourism infrastructure, including food service establishments and banking services (ATMs), and evaluates their accessibility through the application of matrix-based methods. The research employs geoinformatics and cartographic tools to perform the spatial analysis and visualization of tourism-related data. This methodological approach enables the identification of spatial interdependencies and enhances the accuracy of analytical outcomes. As a result, an analysis of the spatial distribution of banking ATMs was conducted using the ArcGIS Pro software through the OD Cost Matrix tool, based on the case of Yerevan City. This tool makes it possible to identify and measure the least-cost paths along a network from multiple origins to multiple destinations. The results indicate that matrix-based methods constitute effective instruments for managing tourism flows and destination attractiveness and can be applied not only within the Tourism Committee of the RA but also by Destination Management Organizations (DMOs) and non-governmental organizations (NGOs).
Keywords: matrix; tourism; OD cost matrix; Confusion Matrix; ArcGIS Pro